The Role of Silent Way Method to English Teaching in a Private Islamic Middle School - Agus Budiharto (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2018)
In the third millennium of quickly globalized world, teaching English as a Foreign Language (EFL) in Indonesia has become a considerable important thing. In this regard, the English teacher plays a key role to attain success in the process of EFL teaching-learning in the classroom. To reach it, the teacher surely needs an appropriate and effective teaching method to be implemented. The present investigation attempts to discuss concerning the roles of Silent Way Method (SWM) as the appropriate method to English teaching. The SWM was implemented in MTS Mifatahul Ulum Pagendingan, as one of private Islamic middle schools in Pamekasan Madura-East Java, for the first grade, by employing the color rods as a visual aid in EFL teaching. The results of this study suggest that SWM was utilized by the tutor in the school could create the students possessed a number of skills in producing EFL.